2005
DOI: 10.1117/12.616888
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and transport properties of Nb-doped SrTiO 3 thin films

Abstract: Nb-doped SrTiO3 epitaxial thin films have been prepared on (001) SrTiO3 substrates using pulsed laser deposition. A high substrate temperature (>1000• C) was found to be necessary to achieve 2-dimensional growth. Atomic force microscopy reveals atomically flat surfaces with 3.9Å steps. The films show a metallic behavior, residual resistivity ratios between 10 and 100, and low residual resistivity of the order of 10 −4 Ωcm. At 0.3 K, a sharp superconducting transition, reaching zero resistance, is observed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, much work is needed to determine whether a temperature dependent Hall factor or two (or multi-) carrier conduction dominates the temperature dependent Hall coefficient, because we have scarce evidence to specify the expression of Hall factor B as a function of temperature, and to testify the existence of two (or multi-) carriers. Takahashi et al [30] reported the temperature dependent Hall coefficient in Nb-doped SrTiO 3 thin films and he supported the argument that temperature dependent Hall coefficient is related to the existence of two types of carriers in doped SrTiO 3 .…”
Section: Hall Measurementmentioning
confidence: 79%
“…However, much work is needed to determine whether a temperature dependent Hall factor or two (or multi-) carrier conduction dominates the temperature dependent Hall coefficient, because we have scarce evidence to specify the expression of Hall factor B as a function of temperature, and to testify the existence of two (or multi-) carriers. Takahashi et al [30] reported the temperature dependent Hall coefficient in Nb-doped SrTiO 3 thin films and he supported the argument that temperature dependent Hall coefficient is related to the existence of two types of carriers in doped SrTiO 3 .…”
Section: Hall Measurementmentioning
confidence: 79%
“…The electrical resistivity of the Nb-STO layer deposited at 800 °C was estimated to be approximately 10 −3 Ω•cm at approximately 77 K. The Nb-STO films deposited by PLD were previously reported in Ref. 18. The Nb-STO film was deposited at a very high temperature of 1300 °C and a low oxygen pressure of 2 × 10 −6 Torr, and then annealed to reoxidize.…”
Section: Nb-sto Conductive Buffer Layers On Textured Copper Tapesmentioning
confidence: 94%